Physiological and metabolic responses in Kök-Börü horses: Correlations with game outcomes - Risvanli, Ali; Sen, Ismail; Canuzakov, Kanat; Tulobayev, Askarbek; Tas, Abuzer; Saklykov, Ruslan; Bayraktar, Metin (Wiley, 2024)
BackgroundThe aim of this study was to examine variations in stress, metabolic, and physiological parameters of horses used in the traditional equestrian team sport of K & ouml;k-B & ouml;r & uuml; in relation to winning and losing outcomes.Material and methodsTo accomplish this, blood samples were taken from horses on four different teams who participated in two separate games, both before and after game. These samples were used to measure levels of cortisol, ACTH, beta-endorphin, adrenaline, noradrenaline, triiodothyronine (T3), and thyroxine (T4) via species-specific commercial ELISA kits. The autoanalyzer tested biochemical and hematological parameters. The gathered data were then analyzed statistically based on the teams' winning or losing status.ResultsThe results suggested that winning teams had lower MID, red blood cell, HGB, RDW-SD, HCT, platelet distribution width, and creatine kinase values post-game in comparison to their pre-game state. Conversely, mean corpuscular hemoglobin concentration (MCHC), mean corpuscular hemoglobin (MCH), and CREA values increased in the winning teams' post-game. Additionally, horses in the winning teams showed a decrease in cortisol, beta-endorphin, and ACTH levels post-game but increased levels of adrenaline and T3. Considering the pre-game values, it was found that GRA and Cl levels were lower in the winning teams. Before the game, adrenaline and T3 levels were higher in the winning teams. No significant difference was observed in post-game hematological parameters between the teams. However, post-game K, adrenaline, and noradrenaline levels were higher among the winning teams' horses, while cortisol and beta-endorphin levels were heightened in horses from the losing side.ConclusionIn conclusion, significant differences were not observed in the distribution of hematological and biochemical parameters of horses following the K & ouml;k-B & ouml;r & uuml; games, regardless of the outcome. However, decreased post-game cortisol, ACTH, and beta-endorphin levels in winning teams may suggest better stress management abilities among these horses. - K & ouml;k-B & ouml;r & uuml;, a favoured traditional equestrian sport in Asia countries.- Stress, metabolic and physiological parameters of horses used in K & ouml;k-B & ouml;r & uuml;.- Winning or losing in K & ouml;k-B & ouml;r & uuml; games does not significantly affect horses' haematological or biochemical parameters. However, horses from winning teams displayed lower post-game levels of cortisol, ACTH and beta-endorphin, suggesting better stress management. image
Keywords: horse; K & ouml;k-B & ouml;r & uuml;; metabolism; physiology; stress